Agonistic Behavior Is Affected by Memory in the Dusky Damselfish Stegastes fuscus - Silveira, M. M.; de Souza, J. F.; Araujo-Silva, H.; Luchiari, A. C. (Frontiers in Behavioral Neuroscience, 2021)
The ability to discriminate familiar from unfamiliar conspecifics has been demonstrated in many species of fish. Agonistic interactions are among the most frequent behaviors exhibited by territorial species and could offer useful information in the individual recognition process. Memory in agonistic situations might modulate the behavioral response and affect social dynamics, but few studies explored the permanence of the memories formed during the aggressive encounters. Here, we investigated the memory retention of an agonistic encounter in the territorial damselfish Stegastes fuscus. The experimental procedure was divided into three parts: (1) Familiarization, (2) Recognition test, and (3) Memory test. For the familiarization phase, fish were visually exposed to the same conspecific for 5 days, 10 min per day, and behavior was recorded. On the following day (conspecific recognition test), half of the animals were paired with the "same conspecific", while the other half was paired with a "different conspecific" for 10 min and behavior was recorded. Fish were retested at intervals of 5, 10, and 15 days after the test to evaluate memory persistence. At the memory test, fish were exposed to the same conspecific as before or to a different conspecific. We found that damselfish reduced the agonistic displays when the stimulus fish was familiar among the memory intervals, but when the fish was unfamiliar, the animals showed a higher aggressive level and only reduced the mnemonic response after 10 days interval. These results suggest that recognition ability in damselfish can be affected by time and modulates agonistic response.